Intensity of The Boarding School in Optimizing (PHBS) Against Continuity of Education in The Environment Community Based on Islamic Boarding Schools in Malang Regency - Husni, Muhammad (Proceedings of Annual Conference on Community Engagement, 2022)
Educational institutions, regardless of their form, aim to transmit knowledge to enlighten the lives of the people and generations of the nation. Boardoing school as an institution of development and empowerment, especially the role of a hard master. The fame of the Islamic Boarding School is determined by the height of the scientific level of the Islamic Boarding School, the great a hard master will be visited by student from various directions in large numbers. Healthy perception according to student is that individuals have physical, healthy, healthy, physically healthy who are not diseased and always healthy, can be active in daily activities. whereas healthy Rokhani is guarding from liver disease. Efforts to establish  the islamic  community, a prosperous future. Health empowerment of Boardoing school -based communities by involving the surrounding community, first providing training and mentoring for the community and student  will be more beneficial. Ideas from the community and facilitators are expected to be able to be applied in the health empowerment of the entire boarding school community. For this reason, it is appropriate to take action in the form of socialization, concrete steps from empowerment, motivation, training education, and partnership cooperation.